The MOCART (Magnetic Resonance Observation of Cartilage Repair Tissue) 2.0 Knee Score and Atlas. (December 2021) - Schreiner, Markus M.; Raudner, Marcus; Marlovits, Stefan; Bohndorf, Klaus; Weber, Michael; Zalaudek, Martin; Röhrich, Sebastian; Szomolanyi, Pavol; Filardo, Giuseppe; Windhager, Reinhard; Trattnig, Siegfried
Objective: Since the first introduction of the MOCART (Magnetic Resonance Observation of Cartilage Repair Tissue) score, significant progress has been made with regard to surgical treatment options for cartilage defects, as well as magnetic resonance imaging (MRI) of such defects. Thus, the aim of this study was to introduce the MOCART 2.0 knee score — an incremental update on the original MOCART score — that incorporates this progression. Materials and Methods: The volume of cartilage defect filling is now assessed in 25% increments, with hypertrophic filling of up to 150% receiving the same scoring as complete repair. Integration now assesses only the integration to neighboring native cartilage, and the severity of surface irregularities is assessed in reference to cartilage repair length rather than depth. The signal intensity of the repair tissue differentiates normal signal, minor abnormal, or severely abnormal signal alterations. The assessment of the variables "subchondral lamina, " "adhesions, " and "synovitis" was removed and the points were reallocated to the new variable "bony defect or bony overgrowth." The variable "subchondral bone" was renamed to "subchondral changes" and assesses minor and severe edema-like marrow signal, as well as subchondral cysts or osteonecrosis-like signal. Overall, a MOCART 2.0 knee score ranging from 0 to 100 points may be reached. Four independent readers (two expert readers and two radiology residents with limited experience) assessed the 3 T MRI examinations of 24 patients, who had undergone cartilage repair of a femoral cartilage defect using the new MOCART 2.0 knee score. One of the expert readers and both inexperienced readers performed two readings, separated by a four-week interval. For the inexperienced readers, the first reading was based on the evaluation sheet only. For the second reading, a newly introduced atlas was used as an additional reference. Intrarater and interrater reliability was assessed using intraclass correlation coefficients (ICCs) and weighted kappa statistics. ICCs were interpreted according to Koo and Li; weighted kappa statistics were interpreted according to the criteria of Landis and Koch. Results: The overall intrarater (ICC = 0.88, P < 0.001) as well as the interrater (ICC = 0.84, P < 0.001) reliability of the expert readers was almost perfect. Based on the evaluation sheet of the MOCART 2.0 knee score, the overall interrater reliability of the inexperienced readers was poor (ICC = 0.34, P < 0.019) and improved to moderate (ICC = 0.59, P = 0.001) with the use of the atlas. Conclusions: The MOCART 2.0 knee score was updated to account for changes in the past decade and demonstrates almost perfect interrater and intrarater reliability in expert readers. In inexperienced readers, use of the atlas may improve interrater reliability and, thus, increase the comparability of results across studies.